A função do manto do reconhecimento na obra como sinthome em Arthur Bispo do Rosário - Livia Eliana de Britto Rios (2007)
In this dissertation on the oeuvre of Arthur Bispo do Rosario, we have considered his artistic productions as a sinthome and intent to demonstrate how his creation of a Recognition Mantle seems to have functioned as an ego that was manufactured by this handcrafter, in anattempt to organize his internal psychotic fragmentation in the Real Register. This Mantle,like a narcissistic paves (shield), an effective defense mechanism of the ego, permitted the Bispo do Rosario to feel protected on the passageway to the new world. In this manner, theBispo tried to circumscribe the Others juissance while also taking pleasure in dressing up as Christ the Redeemer, in his representation of the Almighty on the Final Judgment Day. Research was based on fundamental Lacanian theoretical concepts. Freudian theory was also reviewed, permitting cross-reference between these two authors on consistent psychoanalytical theoretical grounds, in an effort to better comprehend the mysterious compulsion of Bispo do Rosario who strove to reproduce the world in an unending series of objects. We shall also examine the way he procrastinated the death solution, so dealing with the void in the Real Register and, as such, devising a manner to precariously sustain his own life. One can perceive the importance of his oeuvre as a sinthome, in the substitute function, a vital necessity in psychosis. The possibility of applying the Lacanian notion of sinthome, in substitution, is herein discussed according to other nominations that advance beyond the paternal function, editing and sustaining subjectivity and also, attempting to establish social bonds.